Compra compulsiva e a influência do cartão de crédito - Veloso, Cristiane Machado (2009)
Compulsive buying is state of disarray – a disorder of impulse control – which aims to minimize negative fellings. The credit card can be a tool that boosts can be a tool that drives the young people and if there is no control can generate debts, psychological and family problems. In this context, the credit card can be an influential tool for young people with a profile of shoppers. The general objective of this study was to analyze the behavior of compulsive buying in young people and specifically identifies: scores of this group classified as compulsive buyers; the minimum and maximum degrees of compulsivity; and the groups with maximum and minimum . the research was conducted in May – June, 2009 with university students in the city of Fortaleza. The sample, not the type probabilistic was composed of 89 students. The results suggest that in the sample, the students identified with a maximum degree of intensity in the credit card, are in the same group that was closest to the behavior of compulsive buyer.